MENGOBATI PERISTIWA NEGATIF DENGAN TEKNIK PERAWATAN DIRI UNTUK KELUARGA BROKEN HOME - Indah, Nur; Ahmad Zaenuri, Lalu; Maliki (Indonesian Society and Religion Research, 2024)
This paper discusses victims of broken home families caused by uncontrolled negative conditions in East Rasanggaro Hamlet. In this paper the author tries to explain that families who experience broken homes lack knowledge about children and children's mentality, and the child's growth and development process. East Rasanggaro Village is famous for its broken homes, caused by various problems such as emotional instability, lack of communication between children and parents, infidelity, neglected children and economic problems. The author tries to offer alternative solutions using self-care techniques, through self-care techniques; The author found changes in the behavior and household conditions of the families concerned. Apart from the impact of self-care, namely changing behavior in getting used to praying in congregation which was never done before, relationships between families have become more harmonious and can be controlled even though not completely, and they also occasionally spend time together, some families have even been able to resolve family conflicts. by deliberating independently with a cool head without having to involve a third person to help resolve the problem.